Application of Data Mining for Optimal Drug Inventory in a Hospital - Siringo-Ringo, Dewi Sahputri; Tambunan, Razana Baringin Daud; Yulizar, Dian; Daulay, Tri Agustina; Husein, Amir Mahmud (Politeknik Ganesha Medan, 2019)
The Hospital is a health care institution that conducts complete individual health services that provide inpatient, outpatient and emergency services. Drug inventory management is one thing that is very important for the survival of hospitals, management of the supply of medical equipment that is not optimal including medicines will have an impact on medical services as well as economically, because 70% of hospital revenue comes from drugs. In this study we propose data mining with a focus on contributions to the comparison of the K-Means and K-Nearest Neighbor (KNN) algorithms for disease classification, then the classification results are carried out mapping the correlation of diseases with drugs using Apriori, based on the results of testing the K-Means algorithm more accurately compared KNN in the Apriori method to find the relationship of disease with drugs based on the value of support, trust, support value, trust is expected to be a reference for drug purchase recommendations so that there is no excess or emptiness of the drug.